Praktek Pemberian ASI Eksklusif pada Ibu Pekerja di Desa Batusuya Kabupaten Donggala: Practice Of Exclusive Breast Feeding For Working Mothers In Batusuya Village Donggala District - Adhyanti Adhyanti; Dwi Erma Kusumawati; Riska Afifah (Svasta Harena: Jurnal Ilmiah Gizi, 2021)
Breast milk (ASI) is an ideal source of nutrition and the safest food for babies for 0-6 months of life. Basic Health Research Data (Riskesdas) in 2018 shows that the proportion of infants aged 0-6 months who receive exclusive breastfeeding is 74.5%, while those who do not receive exclusive breastfeeding are 25.5%. The purpose of this study was to describe the practice of exclusive breastfeeding for working mothers in Batusuya Village, Sindue Tumbusbora District, Donggala Regency. This type of research is a descriptive study. The population of this study were all working mothers who have children aged 0-6 months. The sample in this study amounted to 60 people. Data analysis in this study used univariate analysis. The results of this study showed that most children were not exclusively breastfed, namely 51 children (85.0%), and only 9 children (15.0%) were exclusively breastfed. Meanwhile, most working mothers are self-employed, namely 34 respondents (56.7%), It can be concluded that most working mothers do not provide exclusive breastfeeding to their children. This is because mothers do not bring their children to work with the percentage (85.0), and most mothers do not know how to store breast milk in the freezer with a percentage (93.3%). Special advice for working mothers to pay more attention to the importance of exclusive breastfeeding.